Business transformation of msmes in the digital era: a qualitative study on cross-functional artificial intelligence integration - Relifra Relifra; Fajri Hamdani; Rakshak Bharti; Dwi Nurhayati (Institute of Computer Science (IOCS), 2026)
This study examines how artificial intelligence (AI) is integrated into managerial routines and business processes of micro, small, and medium-sized enterprises (MSMEs) in the context of digital transformation. Using a qualitative approach, data were collected through semi-structured interviews with ten MSME owners and managers and analyzed using thematic analysis. The findings reveal that AI adoption is driven primarily by pragmatic considerations, particularly tangible business benefits, ease of use, and facilitating conditions, while social influence plays a limited role. More importantly, once AI becomes part of routine practice, its impact extends across marketing, human resources, finance, and operations. The study demonstrates that AI contributes to business transformation by enabling cross-functional integration and more coherent managerial decision-making. These results highlight that the value of AI in MSMEs emerges from its routinized and integrated use rather than from adoption alone